Loved and unloved : the girl child in the family - Bagchi Jasodhara; Guha Jaba; Sengupta Poile (Calcutta : Stree, 1997)
Survey conducted in West Bengal; includes case studies.
Includes index.
Keywords: Girls -- India; Girls -- India -- Social conditions; Girls -- Crimes against -- India